2019
DOI: 10.1111/nicc.12408
|View full text |Cite
|
Sign up to set email alerts
|

Type of admission and nursing workload of critical patients: a cross‐sectional study

Abstract: Background: According to the perception of nurses in the intensive care unit (ICU), surgical patients need more nursing care, thus requiring higher nursing workloads for these patients than those admitted as clinical patients. However, some study results on the relationship between the type of admission and the nursing workload are considered contradictory. Aims and objectives: To identify if the type of admission (clinical, emergency surgery or elective surgery) is a predictive factor of the nursing workload … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
1
9
1
6
Order By: Relevance
“…Além disso, a carga da doença mensurada pelo ICC pode não ser indicador apenas de maior gravidade, mas também da possibilidade de prováveis complicações, uma vez que o paciente pode apresentar maior dificuldade de recuperação, sendo esta acrescida se o paciente for idoso (19) . Já a procedência cirúrgica também compusera a maioria dos internados no ambiente intensivo (8,(12)(13)(14) . O número elevado de pacientes internados no pós-operatório decorre do fato que algumas cirurgias têm como protocolo a vinda do paciente para UTI, pois se exige atenção na evolução, uma vez que complicações são ainda frequentes, ocorrendo em cerca de um terço dos pacientes.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Além disso, a carga da doença mensurada pelo ICC pode não ser indicador apenas de maior gravidade, mas também da possibilidade de prováveis complicações, uma vez que o paciente pode apresentar maior dificuldade de recuperação, sendo esta acrescida se o paciente for idoso (19) . Já a procedência cirúrgica também compusera a maioria dos internados no ambiente intensivo (8,(12)(13)(14) . O número elevado de pacientes internados no pós-operatório decorre do fato que algumas cirurgias têm como protocolo a vinda do paciente para UTI, pois se exige atenção na evolução, uma vez que complicações são ainda frequentes, ocorrendo em cerca de um terço dos pacientes.…”
Section: Resultsunclassified
“…Portanto, observou-se que, embora os pacientes fossem cirúrgicos eletivos e permanecessem pouco tempo na UTI, eles demandaram da equipe de enfermagem tanto quanto os pacientes clínicos. Esta afirmação corrobora com o encontrado em estudo, que evidenciou uma correlação negativa (-0,23) entre o NAS e tempo de internação, ou seja, quanto menor o tempo de internação, maior o NAS (8) .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Romanao et al . () further the exploration by correlating the reason for admission to ICU and nursing workload. In this retrospective cross‐sectional study conducted over 5 months, they concluded that the type of admission had no predicative value in estimating nursing workload.…”
mentioning
confidence: 99%